Effect of motor imagery on excitability of spinal neural function and its impact on the accuracy of movement-considering the point at which subjects subjectively determine the 50%MVC point - Fukumoto, Yuki; Suzuki, Toshiaki; Bunno, Yoshibumi (Journal of Physical Therapy Science, 2016)
[Purpose] This study aimed to examine the effect of motor imagery on the accuracy of motion and the excitability of spinal neural function. [Subjects and Methods] Thirty healthy volunteers (males, 15; females, 15; mean age, 20.3 ± 1.0 years) were recruited. F-waves was recorded at rest, while holding a sensor, and while using motor imagery. Next, subjects learned 50% maximum voluntary contraction. The pinch force was measured without visual feedback before and after motor imagery. F-waves were analyzed with respect to persistence and the F/M amplitude ratio. Correction time and coefficient of variation were calculated from the pinch force. [Results] Persistence and F/M amplitude ratio ware significantly higher in the holding sensor and motor imagery conditions than in the resting condition. In addition, persistence under motor imagery was significantly higher than that in the holding sensor condition. No significant differences were observed in relative values of correction time and coefficient of variation between the two pinch action conditions. The pinch force in task 2 approximated a more authentic 50%MVC than that in task 1. [Conclusion] Motor imagery increases the excitability of spinal neural function, suggesting that it also affects accurate control of muscle force.